Evaluation of an Upgraded Version of the Roche Cobas AmpliPrep/Cobas TaqMan HIV-1 Test for HIV-1 Load Quantification - Damond, F. (American Society for Microbiology (ASM), 2010)
We evaluated the performance of the prototype Cobas AmpliPrep/Cobas TaqMan HIV-1 test, version 2.0, using prospective and archived clinical samples initially underquantitated by the Cobas AmpliPrep/Cobas TaqMan HIV-1 test. The performance of the new test was significantly improved, and the majority of the underquantitation observed with the first-version test was eliminated.